Effect of Integrated Reproductive Health Learning Module Application on Student’s Motivation and Learning Satisfaction in Junior High School - Fitria Fitria; Benny Hasan Purwara; Vita Murniati Tarawan (Global Medical & Health Communication (GMHC), 2019)
One of the potential public health issues in Indonesia is adolescent reproductive health (ARH) issue, particularly premarital sex and promiscuity behaviors which create the risk for unwanted pregnancies and sexual transmitted diseases such as HIV and AIDS. This study aimed to increase in student’s motivation and learning satisfaction through the application of integrated reproductive health learning module in junior high school. This was a pre- and post-test quasiexperimental study with control group design on 358 seventh grade junior high school students in Bandung city. Sampling was performed using multistage random sampling method and subjects were divided equally into treatment group (n=179) and control group (n=179). Data collected were analyzed using chi-square test, Wilcoxon test, and Mann-Whitney test. Results showed that the application of integrated reproductive health learning module influenced motivation and satisfaction, which was evident from the increase in motivation and learning satisfaction scores in the treatment group (21.9% and 6.23%) when compared to the control group (2.2% and 6.1%). In conclusions, the use of integrated reproductive health learning module significantly influences student’s motivation and learning satisfaction among seventh grade junior high school students. PENGARUH PENERAPAN MODUL PEMBELAJARAN KESEHATAN REPRODUKSI TERINTEGRASI TERHADAP MOTIVASI DAN KEPUASAN BELAJAR SISWA DI SEKOLAH MENENGAH PERTAMASalah satu permasalahan kesehatan masyarakat yang potensial di Indonesia adalah masalah kesehatan reproduksi remaja (KRR) khususnya perilaku seks pranikah dan pergaulan bebas yang berisiko kehamilan yang tidak diinginkan dan penyakit infeksi menular seksual (IMS) seperti HIV dan AIDS. Penelitian ini bertujuan meningkatkan motivasi dan kepuasan belajar siswa dengan menerapkan modul pembelajaran kesehatan reproduksi terintegrasi di sekolah menengah pertama (SMP). Penelitian ini menggunakan pre- and post-test quasi-experimental study dengan desain kelompok kontrol pada 358 siswa kelas tujuh SMP di Kota Bandung pada Maret–April 2017. Pengambilan sampel dilakukan menggunakan metode multistage random sampling dan subjek dibagi secara merata menjadi kelompok perlakuan (n=179) dan kelompok kontrol (n=179). Data yang dikumpulkan dianalisis menggunakan uji chi-square, uji Wilcoxon, dan uji Mann-Whitney. Hasil penelitian menunjukkan bahwa penerapan modul pembelajaran kesehatan reproduksi terintegrasi memengaruhi motivasi dan kepuasan belajar yang terbukti dari peningkatan motivasi dan skor kepuasan belajar pada kelompok perlakuan (21,9% dan 6,23%) bila dibanding dengan kelompok kontrol (2,2% dan 6,1%). Simpulan, penerapan modul pembelajaran kesehatan reproduksi terintegrasi secara signifikan memengaruhi motivasi dan kepuasan belajar siswa kelas tujuh SMP.